High-purity aluminum oxide ceramic substrate capable of being used for Ka wave band and preparation method of high-purity aluminum oxide ceramic substrate

By mixing the doping modifier with part of the alumina in advance and pre-sintering, the problem of poor sintering density of high-purity alumina ceramic substrate is solved, and the high-frequency electrical performance is improved and the Ka band stability is achieved. Performance performance.

CN119462086APending Publication Date: 2025-02-18CHENGDU HONGMING & UESTC NEW MATERIALS

Patent Information

Application Number
CN202411339171.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-02-18

Smart Images

  • Figure CN119462086A_ABST
    Figure CN119462086A_ABST
Patent Text Reader

Abstract

The invention discloses a high-purity aluminum oxide ceramic substrate capable of being used for a Ka wave band and a preparation method of the high-purity aluminum oxide ceramic substrate, and relates to the field of ceramic substrates and preparation methods of the ceramic substrates. The ceramic substrate material is composed of a main body aluminum oxide and a composition, and the composition comprises a doping modifier and a part of aluminum oxide; the ratio of the doping modifier to part of aluminum oxide is 1: n; wherein 2 < = n < = 8; the composition accounts for less than or equal to 0.4% of the total amount of the ceramic substrate raw materials. According to the aluminum ceramic material, the doping modifier and part of aluminum oxide are pre-synthesized into a composition, the probability that aluminum oxide powder particles make contact with composition particles is increased, and the doping modification effect is improved. 1 part of doping modifier and n parts of aluminum oxide are uniformly mixed and pre-synthesized into a composition, so that the doping modification effect and the cooling effect are improved, and the combining capacity of composition particles and aluminum oxide particles in the subsequent synthesis process is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic substrate materials and preparation methods thereof, and in particular to a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof. Background Art

[0002] The rapid development of modern electronic information technology has promoted the miniaturization, portability and multifunctionality of electronic products. Substrate materials should meet the following performance requirements: 1) excellent electrical properties; 2) good appearance characteristics, as a substrate material, to ensure that the functions of electronic components or printed circuits are not affected; 3) good high-frequency characteristics to meet the requirements of high-speed transmission. There are many types of substrate materials, including alumina ceramic substrates, aluminum nitride ceramic substrates, beryllium oxide ceramic substrates, silicon carbide substrates, silicon nitride substrates, sapphire substrates, etc., and even epoxy glass, diamond, metal and metal-based composite materials. Among them, alumina ceramic substrates are the most mature ceramic materials with good comprehensive performance in the current electronics industry due to their low cost, high strength, high hardness, good chemical stability and heat shock resistance, good insulation and adhesion to metal, accounting for 90% of the total ceramic substrates.

[0003] The electrical properties and high-frequency characteristics of alumina ceramic substrates are related to their purity. High-purity alumina ceramics usually need to be sintered at a temperature higher than 1600°C to be dense. Higher sintering temperatures may cause abnormal growth of alumina crystals and reduce the degree of densification of the sintered body, thus affecting the performance of high-purity alumina ceramics. Reducing the average size of powder particles and adding appropriate additives can reduce the sintering temperature of high-purity alumina ceramics, but will affect its high-frequency electrical properties. Applications such as thin-film circuits and packaging substrates have very high requirements for their high-frequency performance. Therefore, it is very necessary to prepare high-purity alumina with good high-frequency electrical properties.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The object of the present invention is to provide a high-purity alumina ceramic substrate (purity ≥ 99.6%) that can be used in the Ka band and a preparation method thereof to obtain good high-frequency electrical properties.

[0006] The present invention is implemented by the following technical solutions: In the first aspect, a high-purity alumina ceramic substrate (purity ≥ 99.6%) that can be used in the Ka band, the material characteristics of the ceramic substrate include:

[0007] The ceramic substrate material consists of main alumina + composite;

[0008] The composition comprises two parts: a doping modifier and a portion of aluminum oxide;

[0009] In the composition, the ratio of the doping modifier to the portion of the aluminum oxide is 1:n; wherein 2≤n≤8;

[0010] The proportion of the doping modifier in the composition to the total amount of the raw materials of the ceramic substrate is ≤0.4%.

[0011] Preferably, the doping modifier includes one or a combination of calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide, and zinc oxide.

[0012] Preferably, the ratios of calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide and zinc oxide are: (0-20): (0-40): (0-40): (0-50): (0-30): (0-10): (0-10).

[0013] Preferably, the sum of lanthanum trioxide and samarium trioxide in the composition accounts for 0 to 0.36% of the total amount of raw materials for the ceramic substrate.

[0014] Preferably, the ratio of magnesium oxide to the sum of calcium oxide, magnesium oxide and silicon dioxide in the composition is ≤ 1 / 3.

[0015] Preferably, the ratio of the sum of zirconium dioxide and zinc oxide in the composition to the total amount of raw materials of the ceramic substrate is ≤0.1%.

[0016] Preferably, the ratio of silicon dioxide to calcium oxide in the composition is 1.56 to 2.16.

[0017] Preferably, the value of n in the composition satisfies: 2≤n≤5.

[0018] The synthesis process of the composite of the ceramic substrate material is as follows:

[0019] S1: weigh 1 part of doping modifier and n parts of aluminum oxide;

[0020] S2: Mixing and ball milling with alcohol as the medium for drying, and calcination at (1050±100)℃ for pre-synthesis;

[0021] S3: ball milling or sand milling, material: ball: alcohol ratio is 1:5:(1.5~3), and the particle size distribution meets (D 90 -D 10 ) / 2D 50 It is a composite of (1.00±0.10).

[0022] On the other hand, a high-purity alumina ceramic substrate (purity ≥ 99.6%) that can be used in the Ka band, the preparation method of the ceramic substrate is characterized by:

[0023] S1: Add the composite and the main material aluminum oxide into the mixing tank of the sand mill, add the solvent, and perform sand milling cycles (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3);

[0024] S2: Vacuum degassing to achieve appropriate viscosity (8000-20000) cp;

[0025] S3: tape casting to obtain a film with a thickness of (165±5) μm, and stacking and cutting to prepare a green sample;

[0026] S4: Sintering at a temperature of (1450±50)°C to obtain a ceramic substrate that meets the requirements.

[0027] Compared with the prior art, the embodiments of the present invention have the following advantages and beneficial effects:

[0028] 1. The high-purity alumina ceramic substrate of the embodiment of the present invention is pre-synthesized by mixing the doping modifier with part of the alumina in advance, thereby increasing the probability of the alumina powder particles contacting the doping modifier particles and improving the doping modification effect. One part of the doping modifier and n parts of alumina are evenly mixed and pre-synthesized into a composite, and the 1 part of the doping modifier in the original high-purity alumina ceramic substrate is enlarged to (1+n) parts of the composite. On the one hand, the proportion of composite particles in the high-purity alumina is increased, and the chance of the alumina particles contacting the composite particles is increased, thereby improving the doping modification effect and the cooling effect. On the other hand, the composite is pre-synthesized with alumina in advance to enhance the binding energy of the composite particles in the subsequent synthesis with the alumina powder. Adding the doping modifier in the form of a composite is more uniform than directly adding the doping modifier.

[0029] 2. The embodiment of the present invention develops a high-purity alumina (purity ≥ 99.6%) ceramic substrate material, wherein at 1 MHz, the dielectric constant is 9.9±0.2, and the dielectric loss tanδ≤0.0001; at 1.9 GHz, ε is 9.9±0.2, and tanδ≤0.00015; at 5.1 GHz, ε is 9.9±0.2, and tanδ≤0.0002; at 10 GHz, ε is 9.9±0.2, and tanδ≤0.00025; at 15 GHz, ε is 9.9±0.2, and tanδ≤0.0003.

[0030] 3. The high-purity alumina (purity ≥ 99.6%) ceramic substrate material for Ka band developed in the embodiment of the present invention has a dielectric constant ε of 9.736-9.996, Δε of 0.257, and a dielectric loss tanδ of (0.404-2.40)×10 -4 .

[0031] 4. The high-purity alumina ceramic substrate developed in the embodiment of the present invention satisfies the following properties at the same time: three-point bending strength σ≥550MPa, thermal expansion coefficient α l (20~950℃):(8.2±0.5)×10 -6 / ℃, thermal conductivity K≥26W / m·K, providing a better basis for high frequency use. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0033] Figure 1 is a schematic diagram of a composite in an embodiment of the present invention;

[0034] Figure 2 This is the element distribution diagram of the high-purity alumina ceramic substrate with direct addition of doping modifiers, where Figure 2 a is the distribution diagram of Al element, Figure 2 b is the distribution diagram of Si element, Figure 2 c is the distribution diagram of La element;

[0035] Figure 3 The element distribution diagram of the high-purity alumina ceramic substrate synthesized in advance, wherein Figure 3 a is the Al element distribution diagram, Figure 3 b is the Si element distribution diagram, Figure 3 c is the La element distribution diagram;

[0036] Figure 4 is a flow chart for preparing the synthetic compound in the embodiment of the present invention;

[0037] Figure 5 The dielectric constant and dielectric loss diagram of the high-purity alumina ceramic substrate at high frequency of Example 3 of the present invention;

[0038] Figure 6 This is a front morphology (30,000 magnification) image of a high-purity alumina ceramic substrate according to Example 3 of the present invention;

[0039] Figure 7 This is a reverse morphology (30,000 magnification) image of the high-purity alumina ceramic substrate of Example 3 of the present invention;

[0040] Figure 8 This is the Al element distribution diagram of the front side of the high-purity alumina ceramic substrate of Example 3 of the present invention.

[0041] Fig. 9 This is the Al element distribution diagram of the reverse side of the high-purity alumina ceramic substrate of Example 3 of the present invention;

[0042] Fig.10 This is a Si element distribution diagram of the front side of the high-purity alumina ceramic substrate of Example 3 of the present invention;

[0043] Fig.11 This is a Si element distribution diagram of the reverse side of the high-purity alumina ceramic substrate of Example 3 of the present invention;

[0044] Fig.12 This is a La element distribution diagram of the front side of the high-purity alumina ceramic substrate of Example 3 of the present invention;

[0045] Fig.13 This is the La element distribution diagram of the back side of the high-purity alumina ceramic substrate of Example 3 of the present invention. DETAILED DESCRIPTION

[0046] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0047] Therefore, the detailed description of the embodiments of the present invention provided below is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0048] The embodiment of the present invention provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, comprising the following steps:

[0049] S1: Weighing a portion of alumina and a doping modifier and then ball milling, drying, calcining, ball milling or sand milling to obtain a composite; including mixing and ball milling with alcohol as a medium, and then drying and calcining at (1050±100)℃ for pre-synthesis, and finally ball milling or sand milling to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The synthetic compound is 1.00±0.10; (Synthesis principle diagram as shown in Figure 1 (shown)

[0050] S2: Add the synthetic material, main alumina and solution (ethanol + ethyl acetate + toluene) into the mixing tank of the sand mill, and perform sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3);

[0051] S3: vacuum degassing to control the viscosity of the slurry to 8000cp~20000cp, and obtain a ceramic diaphragm with a designed thickness of (165±5)μm by casting;

[0052] S4: cutting the ceramic diaphragm stack into green samples, and sintering at (1450±50)° C. to obtain a ceramic substrate.

[0053] Among them, the doping modifier includes one or more combinations of oxides such as calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide, zinc oxide, etc., and oxides such as calcium oxide, magnesium oxide, silicon dioxide, zinc oxide, etc. act as glass phase components to cool down, and oxides such as calcium oxide, magnesium oxide, lanthanum trioxide, samarium trioxide, zirconium dioxide, etc. play the roles of crystallization refinement, toughening, and densification.

[0054] The raw materials include calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide, zinc oxide, etc. with a purity greater than 99%, and the purity of alumina (including main alumina and alumina in the composite) is not less than 99.99%.

[0055] Since the purity of alumina in high-purity alumina ceramic substrates is ≥99.6%, the sum of oxides such as CaO, MgO, SiO2, La2O3, Sm2O3, ZrO2, and ZnO in the doping modifier does not exceed 0.4%, and the proportion of each oxide is at the ppm level. It is difficult to ensure the uniformity of the mixture in engineering applications, which is fatal to the performance uniformity of high-purity materials. With a very small amount of impurity particles in a large amount of alumina powder, it is difficult to ensure that the probability of each alumina powder particle in the high-purity alumina ceramic substrate material contacting the doping modifier particles is the same. Impurity particles are difficult to disperse evenly, so the doping modification and liquid phase cooling caused by the impurities are difficult to play a role evenly.

[0056] Therefore, the embodiment of the present invention adopts the design idea of ​​impurity doping + glass phase cooling + adding aluminum oxide to amplify - pre-synthesis, and the doping modifier is mixed with part of the aluminum oxide in advance for pre-synthesis and amplification to obtain a synthetic material (synthesis principle as shown in Figure 1 As shown), the probability of alumina powder particles contacting the composite particles is increased, and the effect of doping modification is improved. Evenly mixing 1 part of doping modifier and n parts of alumina and pre-synthesizing them into a composite is equivalent to enlarging 1 part of doping modifier in the original high-purity alumina ceramic substrate to (1+n) parts of the composite. On the one hand, the proportion of composite particles in the high-purity alumina ceramic substrate is increased, and the chance of alumina particles contacting the composite particles is increased, thereby improving the doping modification effect and the cooling effect; on the other hand, pre-synthesis with doped alumina in advance enhances the ability of the composite particles to be subsequently synthesized with the main alumina powder.

[0057] Example 1

[0058] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0059] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 10 parts of CaO, 20 parts of MgO, 30 parts of SiO2, 20 parts of La2O3, 15 parts of Sm2O3, 2.5 parts of ZrO2, and 2.5 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:2; the doping modifier accounts for 0.4% of the total raw materials of the ceramic substrate.

[0060] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0061] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0062] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0063] Example 2

[0064] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0065] Weigh the composite (doping modifier and partial alumina) and main alumina, the doping modifier includes 15 parts of CaO, 25 parts of MgO, 40 parts of SiO2, 15 parts of La2O3, 5 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:3; the doping modifier accounts for 0.3% of the total raw materials of the ceramic substrate.

[0066] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0067] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0068] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0069] Example 3

[0070] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0071] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 30 parts of MgO, 40 parts of SiO2, 5 parts of La2O3, 5 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:3; the doping modifier accounts for 0.4% of the total raw materials of the ceramic substrate.

[0072] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0073] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0074] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0075] Example 4

[0076] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0077] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 40 parts of MgO, 40 parts of SiO2, 0 parts of La2O3, 0 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:5; the doping modifier accounts for 0.3% of the total raw materials of the ceramic substrate.

[0078] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0079] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0080] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0081] Example 5

[0082] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0083] Weigh the composite (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 30 parts of MgO, 40 parts of SiO2, 5 parts of La2O3, 5 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:5; the doping modifier accounts for 0.4% of the total raw materials of the ceramic substrate.

[0084] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0085] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0086] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0087] Example 6

[0088] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0089] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 30 parts of MgO, 40 parts of SiO2, 2.5 parts of La2O3, 2.5 parts of Sm2O3, 2.5 parts of ZrO2, and 2.5 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:2; the doping modifier accounts for 0.3% of the total raw materials of the ceramic substrate.

[0090] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0091] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0092] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0093] Example 7

[0094] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0095] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 0 parts of CaO, 0 parts of MgO, 0 parts of SiO2, 50 parts of La2O3, 30 parts of Sm2O3, 10 parts of ZrO2, and 10 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:3; the doping modifier accounts for 0.2% of the total raw materials of the ceramic substrate.

[0096] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0097] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0098] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0099] Example 8

[0100] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0101] Weigh the composite (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 30 parts of MgO, 40 parts of SiO2, 5 parts of La2O3, 5 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:8; the doping modifier accounts for 0.2% of the total raw materials of the ceramic substrate.

[0102] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0103] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0104] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0105] Example 9

[0106] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0107] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 0 parts of CaO, 0 parts of MgO, 0 parts of SiO2, 50 parts of La2O3, 30 parts of Sm2O3, 10 parts of ZrO2, and 10 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:5; the doping modifier accounts for 0.4% of the total raw materials of the ceramic substrate.

[0108] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0109] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0110] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0111] Example 10

[0112] This embodiment provides a high-purity alumina ceramic substrate that can be used in the Ka band and a preparation method thereof, including the following contents:

[0113] Weigh the synthesis (doping modifier and partial alumina) and main alumina, the doping modifier includes 20 parts of CaO, 30 parts of MgO, 40 parts of SiO2, 5 parts of La2O3, 5 parts of Sm2O3, 0 parts of ZrO2, and 0 parts of ZnO, and the ratio of the doping modifier to the partial alumina is 1:2; the doping modifier accounts for 0.3% of the total raw materials of the ceramic substrate.

[0114] Using alcohol as a medium, the doping modifier and part of the alumina are mixed in a ratio of material: ball: alcohol = 1:5:2 and ball milled for (6±0.5)h, and then dried and calcined at a temperature of (1050±100)℃ for pre-synthesis, and ball milled or sand milled to obtain a particle size distribution satisfying (D 90 -D 10 ) / 2D 50 The doping material is about 1.00±0.10 (the preparation flow chart of the composite is as follows Figure 4 shown).

[0115] Add the synthetic material, main alumina and solvent into the mixing tank of the sand mill, and carry out sand milling cycle (10 to 30) times, each time for (8 to 20) minutes according to the ratio of material: ball: solution = 1:5: (1.5 to 3).

[0116] The viscosity of the slurry is controlled at 8000cp~20000cp by vacuum degassing, and a ceramic diaphragm with a designed thickness of (165±5)μm is obtained by tape casting. The ceramic diaphragm is stacked and cut in a certain way to prepare a green sample, and sintered at (1450±50)℃ to obtain a ceramic material.

[0117] Test results

[0118] The element distribution diagram of the high-purity alumina ceramic substrate with direct addition of doping modifiers and additives is shown in Figure 2 and Figure 3 As shown. Figure 2 and Figure 3 By comparison, it is found that the element distribution in the embodiment of the present invention where the composite is added is more uniform than that in the embodiment where the doping modifier is directly added.

[0119] The topography scans were performed on the front and back surfaces of the high-purity alumina ceramic substrate of Example 3. The results are as follows: Figure 6 and 7 As shown. Figure 6 and Figure 7 It can be seen that the morphology of the front and back surfaces of the substrate has the same grain size and is dense. The front and back elements of the substrate are scanned, and the front and back element distribution mapping diagrams of Al, Si and La are shown as follows: Figure 8-13 As shown, the element distribution is basically the same, and it also shows that the cooling, doping and densification effects are basically the same. In the embodiment of the present invention, through the design ideas and preparation methods of the composite, the doping modifier and part of the alumina powder are pre-synthesized in advance to ensure that the probability of contact between the alumina particles and the composite powder particles is basically the same, ensuring the uniformity of the element distribution in the high-purity alumina substrate, thereby obtaining good high-frequency performance.

[0120] The high-purity alumina ceramic substrates of Examples 1 to 10 were subjected to performance tests such as dielectric constant, dielectric loss, flexural strength, thermal expansion coefficient, etc. at different frequencies. The dielectric properties of the ceramic substrates were tested using a resonant cavity method, including the dielectric properties at test frequencies of 1 MHz, 1.9 GHz, 5.1 GHz, 10 GHz, and 15 GHz, and the dielectric constant and dielectric loss at continuous frequencies in the range of (22.5 to 42.8) GHz. The substrate performance test results are shown in Table 2 below.

[0121] The proportions of the raw materials and the proportions of the doping modifiers in the compositions of Examples 1 to 10 are shown in Table 1.

[0122] Table 1 Ratio of each raw material and proportion of doping modifier in the composite

[0123]

[0124]

[0125] Table 2 Performance test results of high purity alumina ceramic substrate

[0126]

[0127]

[0128] Figure 5 The following is a curve diagram showing the change in dielectric constant and dielectric loss of the high-purity alumina ceramic substrate of Example 3 at a frequency of (22.5-42.8) GHz. Figure 5 As shown in Table 2, the high-purity alumina ceramic substrate of the embodiment of the present invention has a dielectric constant of 9.9±0.2, a dielectric loss tanδ≤0.0003, and a thermal expansion coefficient (20~950℃) of (8.2±0.5)×10 at frequencies of 1MHz, 1.9GHz, 5.1GHz, 10GHz, 15GHz, and (22.5~42.8)GHz. -6 / ℃, flexural strength σ≥550MPa, thermal conductivity K≥26W / m·K, which can meet high-frequency use, and the dielectric constant and dielectric loss both maintain stable changes.

[0129] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-purity alumina ceramic substrate that can be used in the Ka band, with an alumina purity of ≥99.6%, characterized in that: It includes a main body of aluminum oxide and a composite composition; The composition comprises a doping modifier and a portion of aluminum oxide; In the composition, the ratio of the doping modifier to the portion of the aluminum oxide is 1:n; wherein 2≤n≤8; The proportion of the doping modifier in the composition to the total amount of the raw materials of the ceramic substrate is ≤0.4%.

2. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 1, characterized in that: The doping modifier includes one or a combination of calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide, and zinc oxide.

3. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 2, characterized in that: The ratio of calcium oxide, magnesium oxide, silicon dioxide, lanthanum trioxide, samarium trioxide, zirconium dioxide and zinc oxide is 0-20:0-40:0-40:0-50:0-30:0-10:0-10.

4. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 3, characterized in that: The sum of lanthanum trioxide and samarium trioxide in the composition accounts for 0 to 0.36% of the total amount of raw materials of the ceramic substrate.

5. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 3, characterized in that: The ratio of magnesium oxide to the sum of calcium oxide, magnesium oxide and silicon dioxide in the composition is ≤1:

3.

6. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 3, characterized in that: The sum of zirconium dioxide and zinc oxide in the composition accounts for less than or equal to 0.1% of the total amount of raw materials of the ceramic substrate.

7. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 3, characterized in that: The ratio of silicon dioxide to calcium oxide in the composition is 1.56 to 2.16:

1.

8. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 1, characterized in that: The value of n in the composite satisfies: 2≤n≤5.

9. The high-purity alumina ceramic substrate applicable to the Ka band according to claim 1, characterized in that: The composition comprises the following steps: S1: weigh 1 part of doping modifier and n parts of aluminum oxide; S2: Using alcohol as the medium, the mixture was ball-milled for 6 h ± 0.5 h in a ratio of material: ball: alcohol = 1:5:2, and then dried and calcined at 1050 ° C ± 100 ° C for pre-synthesis; S3: Use alcohol as the medium, and perform ball milling or sand milling according to the ratio of material: ball: alcohol = 1:5:2, and dry to obtain a particle size distribution that meets (D 90 -D 10 ) / 2D 50 The composite is 1.00±0.

10.

10. A method for preparing a high-purity alumina ceramic substrate that can be used in the Ka band as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Add the synthetic material, main alumina and solution (ethanol + ethyl acetate + toluene) into the mixing tank of the sand mill, and perform sand milling for 10 to 30 times according to the ratio of material: ball: solution = 1:5: (1.5 to 3), and perform sand milling for 8 to 20 minutes each time for grinding and dispersion; S2: Vacuum degassing to control the viscosity of the slurry to 8000cp~20000cp; S3: Controlling the casting parameters to obtain a ceramic diaphragm with a thickness of 165±5 μm, and cutting the ceramic diaphragm stack into a green sample; S4: The sintering temperature is 1450±50°C, and a ceramic substrate is obtained by sintering.

Citation Information

Patent Citations

  • Aluminum oxide ceramic substrate with high heat conductivity and preparation method thereof

    CN103408291A

  • Method for producing aluminum nitride ceramic substrate by adopting composite powder grain shape

    CN106588025A

  • 99.6 percent-Al2O3 ceramic substrate thinning method

    CN107117946A

  • High-strength low-dielectric microwave dielectric ceramic material and preparation method thereof

    CN116924784A

  • Raw material powder for forming ceramic substrate and production of ceramic substrate using the raw material powder

    JP1992193761A

Cited By

  • Alumina ceramic substrate material as well as preparation method and application thereof

    CN121107828A

  • An alumina ceramic substrate material, its preparation method and use

    CN121107828B

  • Preparation method of 96 aluminum oxide ceramic substrate

    CN121362033A